Anatomia de uma misura : imaginário, criação e pesquisa - Santos, Carla Priscila Antunes dos (2023)
This research presents the homology of an investigation process about the birth of a “misura” (haunting) named “Bird-people” in my creations and its consequences in my arteducational work, in my training as a researcher and in the personal elaboration of a grieving process. The gestation of the Bird-people led all the layers of this research. The theoretical basis was built essentially from the foundations of the imaginary (Danielle Rocha Pitta/Gilbert Durand). The procedures performed were the result of the confluence of methods from cartography (Virgínia Kastrup), artography (Belidson Dias) and mythology (Danielle Pitta, Gilbert Durand and Yves Durand). Based on the mythocriticism of my artistic production and the highlighting of the mythical redundancies and main meanings that make up my imagination, I share how these symbolic elements were related to my dimensions as an art educator, researcher and neurodivergent person, which offered possible clues and strategies about the relationship: imaginary, creation and arteducational research.